The Effect of Health Claims on Television Commercials toward Consumer’s Decision Making in Food Product Buying (Case Study in Yogyakarta City) - Yuni Retnowati (The Indonesian Journal of Communication Studies, 2009)
Advertisement is a medium to declare claims based on product benefits. However, there are times where the claims are not supported by evidence, hence mislead and confuse consumers in buying the products. Health issues discussed in public sphere are used to show the product benefits compare to other competitors. The aims of this research were to study consumer’s perception toward health claims on TV commercials and the effect of health claims on TV commercials (external factor) and internal factors toward consumer’s decision making in food product buying. Path analysis was used to analyze the effect of external and internal factors. The result of this research shows that consumer’s perception toward health claims on food product TV commercials is easy to understand, attractive, believable and suitable for the condition and the needs of consume, therefore its perception able to influence buying decision making (buying intensity). Food product includes in this category was food fiber which helped metabolism and natural diet. Consumers who attain the age of 21–50 years old, married, working and have good knowledge of nutrient are often do the buying activity.